Medicinal fungus Phellinus igniarius alleviates gout in vitro by modulating TLR4/NF-kB/NLRP3 signaling - Zhou, Xuebin; Shi, Qiyuan; Li, Jinhua; Quan, Shengli; Zhang, Xinyue; Gu, Lili; Li, Hongxing; Ju, Yue; Hu, Min; Li, Qin (Frontiers in Pharmacology, 2022)
Background: Phellinus igniarius (P. igniarius) is a valuable medicinal and edible fungus with various biological activities such as anti-inflammation, antioxidation, and immune regulation. In this study, we explored the effects of P. igniarius on a gout model in vitro. Methods: The DPPH, ABTS, and FRAP methods were combined to determine and compare the antioxidant activities of wild P. igniarius total polyphenols (WPP) and cultivated P. igniarius total polyphenols (CPP) in vitro. Spectrophotometry was used to compare the inhibitory effect of WPP and CPP on xanthine oxidase (XO) activity to evaluate antihyperuricemia activity in vitro. HUVECs were stimulated with monosodium urate (MSU) crystals for 24 h to establish an acute gouty inflammation model in vitro. The protective effects were compared by measuring cell viability; the contents of ICAM-1, IL-1β, IL-6, and VCAM-1; the protein expressions of TLR4 and NLRP3; ROS production; and the nuclear translocation of NF-κB p65. UHPLC-QE-MS technology was used to explore the potential metabolic mechanism of P. igniarius against gout. Results: WPP and CPP had strong antioxidant capacity, and the antioxidant capacity of CPP was similar to that of WPP. In a comparative experiment of XO activity inhibition by WPP and CPP, the IC50 values were 88.19 μg/mL and 108.0 μg/mL, respectively. At a dose of 40 μg/mL, WPP and CPP significantly improved the decrease in cell viability induced by MSU (150 μg/mL) and inhibited the increase in inflammatory factors such as ICAM-1, IL-1β, IL-6, and VCAM-1. The increase in TLR4 and NLRP3 protein expression induced by MSU crystals in HUVECs was also significantly inhibited by total polyphenols from wild and cultivated P. igniarius. In addition, both significantly improved MSU-induced ROS overproduction and NF-κB p65 nuclear translocation. WPP and CPP may primarily be involved in phenylalanine metabolism and lysophosphatidylcholine metabolism in their role in the treatment of gout. Conclusions: CPP and WPP both showed good antioxidant activity and xanthine oxidase inhibitory activity and had good therapeutic effects on the gout model in vitro.